Ketika Fans ‘Menikahi’ Idolanya: Studi Fenomenologi tentang Loyalitas Fandom BTS - Jennifer Riona; Nanang Krisdinanto (Avant Garde, 2021)
This study focuses on the phenomenon of the fandom subculture, namely the behavior of members of the Surabaya Army (a group of fans of the K-Pop BTS group based in Surabaya), especially regarding loyalty to their idol group. This study uses a qualitative approach with a phenomenological method, in which the researcher allows BTS fans to actively interpret their loyalty through their intersubjective, namely their experience of being a fan. The data collection technique was carried out through in-depth interviews to obtain the meaning of loyalty that was told by the Surabaya Army from their own point of view. The results of this study indicate that loyalty to an idol is interpreted as an obligation that must be done sincerely in return for the struggle of his idol. Information technology has also made the relationship between Army Surabaya and its idol transcend real life, which can be seen from the fact that the idol is considered a virtual lover or husband. They have developed a special bond or relationship with their idol group that only themselves can feel. The results also showed that the Surabaya Army loyalty to BTS had reached a stage called The Marriage.